METODE COOPERATIVE LEARNING SEBAGAI SALAH SATU ALTERNATIF METODE PEMBELAJARAN MEMBACA DALAM BAHASA INGGRIS - Syafri, Frimadona (Lembaran Ilmu Kependidikan, 2007)
In the Indonesian school system, English is a compulsory subject taught atvarious education levels with the emphasis on reading and writing skills. In spite ofthe importance of mastering reading and writing skills, most high school students arestill unable to read and comprehend English texts properly. Besides, it is hard for themto write a simple English text appropriately. One possible way to solve the problem isby applying new strategies to improve their reading and writing skills. One of thestrategies that can sufficiently be used is cooperative learning. It is a teachingarrangement that refers to small, heterogeneous groups of students working together toachieve a common goal (Kagan, 1994). There are some types of cooperative learning,one of them is CIRC. This type may be suitable for teaching reading and writing. Itwas shown in the action research involving year VIII students of Isriati Junior HighSchool of Semarang, Indonesia. The study was conducted in five cycles and aiming atknowing the effective interaction in the language classroom. Through theimplementation of the study, the students average scores increased in each cycle.Besides, they looked creative and enthusiastic when they were working in groups.Kata kunci: pembelajaran membaca, metode Cooperative Learning